ANALYSING THE IMPACT OF BRAND EQUITY ON CONSUMER PURCHASE INTENTION OF ETUDE HOUSE COSMETIC PRODUCT IN MANADO - Walangitan, Arindah; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2015)
The high number of imported product sales have made foreign companies became more interested to enter Indonesia’s market, including the Etude House cosmetic producst. In order to maintain the existence of the company, a strong brand equity should be built. Aaker’s brand equity theory is used in this research, involving brand loyalty, brand awareness, perceived quality, and brand association. The purpose of this study is to examine the impact of brand equity on consumer purchase intention. The data collection method used the non probability convenient sampling technique. A sample of 100 questionnaires were distributed to the customer of Etude House in Manado, and multiple regression analysis was used.Previous research from Jalivand, Samiei & Mahdavinia (2011) proves that all the elements of brand equity has a significant influence on consumer purchase intention in automobile industry. The findings of this research shows that simultaneously all the elements of brand equity has a strong influence on customer purchase intention. While partially only perceived quality and brand association influence customer purchase intention, whereas brand loyalty and brand awareness does not have any significant influence on customer purchase intention. Thus, Etude House should build a good relation with the customer to create strong brand loyalty and improve the product’s design to be more attractive and easy to remember by the customers. Keywords : brand equity, purchase intention